Challenges of Developing English Receptive and Productive Skills among Libyan University Students: A Quantitative Study - Mohammed Saleh Alwadi, Asmaa (مجلة العلوم والدراسات الإنسانية - كلية الآداب والعلوم – المرج, 2026)
This study investigates the challenges encountered by Libyan university students in acquiring English language skills, including listening, reading, speaking, and writing. The primary objective is to identify the main factors causing these challenges and explore potential solutions. A quantitative research design was employed, using a self-developed questionnaire consisting of twenty closed-ended questions. The sample included fifty English language students randomly selected from the Faculty of Arts and Sciences, University of Benghazi – Al-Abyar Branch. Data were analyzed using descriptive statistics to determine the most common difficulties faced by students. Findings revealed that students experienced significant challenges in listening and speaking due to limited vocabulary, fear of making mistakes, lack of confidence, and inadequate classroom interaction. Writing difficulties were primarily linked to poor grammar and spelling, while reading challenges stemmed from insufficient educational background and lack of motivation. The study recommends adopting communicative and student-centered approaches to enhance language skill development. These findings provide insights for educators and policymakers to improve English language teaching practices in Libyan higher education contexts.